P-240 Human extracellular vesicles (EVs) secreted by aneuploid embryos potentiate development of non-invasive PGT-A RNA biomarkers and stimulate MUC1 up-regulation in primary endometrial stromal cells (ESCs). (6th August 2021) - Makieva, S; Scotti, G M; Lazarevic, D; Giacomini, E; Ottolina, J; Bartiromo, L; Schimberni, M; Alteri, A; Pavone, V; Minetto, S; Papaleo, E; Morelli, M; et al.
Abstract: Study question: Could EVs secreted by aneuploid embryos a) serve for development of RNA biomarkers for PGT-A and b) elicit a relevant transcriptomic response in decidualised ESCs? Summary answer: Aneuploid embryo EVs a) contain PPM1J, LINC00561, ANKRD34C and TMED10 in differential abundance from euploid EVs and b) induce up-regulation of MUC1 in decidualised ESCs. What is known already: Embryo aneuploidy accounts for approximately 50% of all recurrent implantation failures in women >35 years old. PGT-A identifies euploid embryos to increase implantation probability but the technology is controversial as it requires an invasive embryo biopsy with an elusive long-term biosafety. The development of non-invasive methods to screen out aneuploid embryos is paramount. It is also critical to decode the embryo-endometrial dialog underlying implantation failure. We have previously reported that IVF embryos secrete EVs that can be internalised by ESCs, conceptualising that successful implantation to the endometrium is facilitated by EVs, which may additionally serve as biomarkers of ploidy status. Study design, size, duration: Embryos destined for biopsy on days 5-7 for PGT-A were grown under standard conditions. Spent media (30μl) were collected from euploid (n = 175) and aneuploid embryos (n = 145) at both cleavage (days 1-3) and blastocyst (days 3-5) stage. Media samples from n = 35 cleavage embryos were pooled in order to obtain five euploid and four aneuploidy pools. Blastocyst media were pooled to create one euploid and one aneuploid pool. ESCs were obtained from five women undergoing diagnostic laparoscopy. Participants/materials, setting, methods: The study was realised at a research hospital. EVs were isolated from euploid and aneuploid Day3 pools with differential ultracentrifugation and EV-RNA sequencing was performed following the SMARTer Stranded Total RNA-Seq approach. ESCs were decidualised (E2:10nM, P4:1uM, cAMP:0.5 mM twice every 48 hours) and treated for 24 hours with 50 ng/ml euploid or aneuploid EVs extracted from blastocyst media. RNA sequencing was performed on ESCs following the Truseq RNAseq protocol. Main results and the role of chance: Aneuploid cleavage stage embryos (n = 4) secreted EVs that were less abundant in RNA fragments originating from the genes PPM1J (log2fc=-5.13, p = 0.011), LINC00561 (log2fc=-7.87, p = 0.010) and ANKRD34C (log2fc=-7.30, p = 0.017) and more abundant in TMED10 (log2fc=1.63 p = 0.025) compared to EVs (n = 5) from euploid embryos. Decidualisation per se induced downregulation of MUC1 (log2FC=-0.54, p = 0.0028) in ESCs as prerequisite for the establishment of receptive endometrium. The expression of MUC1 transcript in decidualised ESCs was significantly increased following treatment with aneuploid compared to euploid embryo-secreted EVs (log2FC=0.85, p = 0.0201). Limitations, reasons for caution: The findings of the study may require validation utilising a second cohort of EVs samples. Wider implications of the findings: This discovery that the RNA cargo of EVs secreted from aneuploid cleavage stage embryos is diverse from that of euploid embryos potentiates the development of non-invasive methodology for PGT-A. The upregulation of MUC1 in decidualised ESCs following aneuploid embryo EV treatment proposes a new mechanism underlying implantation failure. Trial registration number: NA